O004/#752 Selection criteria for omitting interval debulking surgery after neoadjuvant chemotherapy for advanced high-grade serous carcinoma of the ovary: KGOG ovsurg-2016/score study. (4th December 2022) - Park, Soo Jin; Lee, Maria; Chung, Hyun Hoon; Kim, Jae-Weon; Park, Noh Hyun; Song, Yong-Sang; Kim, Hee Seung
Abstract : Objectives: This study investigates the selection criteria for omitting interval debulking surgery (IDS) after neoadjuvant chemotherapy (NACT) due to a higher response to chemotherapy for advanced ovarian cancer. Methods: We searched the ovarian, fallopian, or primary peritoneal cancer database registered between January 2000 and May 2021. We included patients with clinical stage III to IV high-grade serous carcinoma of the ovary (HGSC) who received NACT after serial measurement of serum levels of CA-125 regardless of IDS. We calculated the CA-125 ELIMination of Rate Constant K (KELIM) value during two cycles of NACT. Then, we calculated the cut-off values of KELIM for predicting platinum resistance and then evaluated the effect of IDS on progression-free survival (PFS) and overall survival (OS) based on the values. Results: Among 279 patients, 194 (76%) were treated with NACT/IDS, and 61 (24%) were treated with chemotherapy alone. Although NACT/IDS showed better PFS and OS than chemotherapy alone in patients with lower KELIM (<0.95), no difference in survival was shown in higher KELIM (≥0.95). In multivariate analysis, IDS was associated with better OS in Low KELIM patients (hazard ratio [HR], 0.517, p=0.016), while IDS was not associated with better survival in High KELIM patients (HR, 0.739, p=0.390). Also, radiologic complete response (CR) and partial response (PR) were associated with better survival regardless of KELIM score. Conclusions: In conclusion, for stage III/IV HGSC patients presenting higher KELIM (≥0.95), IDS may be omitted when the radiologic CR or PR is accomplished during NACT.